Immunoinformatic Analysis to Identify Proteins to Be Used as Potential Targets to Control Bovine Anaplasmosis - Sergio D. Rodríguez-Camarillo; Rosa E. Quiroz-Castañeda; Hugo Aguilar-Díaz; José E. Vara-Pastrana; Diego Pescador-Pérez; Itzel Amaro-Estrada; Fernando Martínez-Ocampo (International Journal of Microbiology)
Omics sciences and new technologies to sequence full genomes provide valuable data that are revealed only after detailed bioinformatic analysis is performed. In this work, we analyzed the genomes of seven Mexican Anaplasma marginale strains and the data from a transcriptome analysis of the tick Rhipicephalus microplus. The aim of this analysis was to identify protein sequences with predicted features to be used as potential targets to control the bacteria or tick-vector transmission. We chose three amino acid sequences different to all proteins previously reported in A. marginale that have been used as potential vaccine candidates, and also, we report, for the first time, the presence of a peroxinectin protein sequence in the transcriptome of R. microplus, a protein associated with the immune response of ticks. The bioinformatics analyses revealed the presence of B-cell epitopes in all the amino acid sequences chosen, which opens the way for their likely use as single or arranged peptides to develop new strategies for the control and prevention of bovine anaplasmosis transmitted by ticks.